2010
DOI: 10.5152/tjr.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TENS on Pain, Disabiliy, Quality of Life and Depression in Patients with Knee Osteoarthritis

Abstract: Objective: The aim of this randomized controlled trial was to evaluate the effects of transcutaneous electrical nerve stimulation (TENS) on pain, disability, functional performance, quality of life (QoL) and depression in patients with knee osteoarthritis (OA). Materials and Methods: Forty patients with primary knee OA diagnosed according to The American College of Rheumatology criteria were randomized into groups. Patients in the Group 1 received TENS, exercise program and hot pack. Group 2 received placebo T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…And did not respond to medications? In a study conducted with a population comparable with our study, Altay et al (2010) reported similar results. This could be due to either the side effects of drug treatment or because the increase in disease activity and symptoms necessitated increased medication use.…”
Section: Discussionsupporting
confidence: 90%
“…And did not respond to medications? In a study conducted with a population comparable with our study, Altay et al (2010) reported similar results. This could be due to either the side effects of drug treatment or because the increase in disease activity and symptoms necessitated increased medication use.…”
Section: Discussionsupporting
confidence: 90%
“…Altay et al in their study also observed a significant improvement in the VAS pain scores after 3 weeks of treatment (p<0.001) in his both study groups. 18 However, very similar to our study, the active TENS group had a greater improvement at the end of treatment when compared to the control group (p<0.001). In 2012, Atamaz FC et al in their multi center double blind RCT compared the effectiveness of TENS, IFC and SWD against each other and sham intervention with exercise training and education 19 .…”
Section: Discussionsupporting
confidence: 87%
“…This assertion was corroborated by the study of Altay et al, ( 24) who found out the effect of TENS on Pain, Disability, Quality of Life and Depression in Patients with Knee Osteoarthritis and concluded that the addition of TENS to heating modalities and exercise program is more effective in decreasing knee pain and related disability in patients with knee OA. The study by Bal et al, (25) evaluated the long term efficiency of TENS on pain and disability and they found the superiority of TENS over placebo.…”
Section: Discussionmentioning
confidence: 64%